Analisis Isi Edukasi Hamil Diluar Nikah Dalam Film “Jenny Juno” (2005) - Arfian Suryasuciramdhan; Alisya Safira; Febriya Alinda Rahayu; Silvia Putri Anggraeni; Meylia Maulidina (Jurnal Mahasiswa Kreatif, 2024)
This research analyzes the themes and narratives in the Korean film "Jenny Juno". Qualitative analysis methods were used to identify and explore the depth of themes expressed in the movie's narrative. The results highlighted major themes such as adolescent growth, friendship, teenage love, and responsibility. The movie tells the story of two teenagers who are still in school who experience problems beyond the limits, where the two teenagers must be responsible for their actions. This will make teenagers more careful in their relationships. Many parents do not agree with events like this, so parents should pay more attention to their children and teach about sexual education to their teenagers. The complex narrative and complex characters in the film were also explored to understand how these themes manifested in the story. The findings provide insight into how the film responds to and reflects relevant social and psychological issues in the Korean cultural context.